Design of BPJS Participant Patient Referral Information System - Tri Cicik Wijayanti; Brian Sebastian Salim; Nur Sucahyo; Albertus Dwiyoga Widiantoro; Edi Wahyu Wibowo (Universitas Dharma Wacana, 2022)
BPJS, Social Security Administrator, is a state-owned health insurance company previously serving as PT. ASKES (Health Insurance), whose services are implemented in several health agencies in Indonesia. One example is hospitals. In doing the community to provide complete individual health services, the Hospital is one of the health agencies supporting the BPJS (Social Security Administrator) program. One of the hospitals that participated in realizing and launching the BPJS program was the XYZ Hospital in AA City. Currently, in managing one of the BPJS social security programs, XYZ Hospital is still manually processing data in the patient referral process, namely by still using patient referral letters. That is what is being demanded by researchers to realize this study's objectives, namely design, a system where later patient referral data can be computerized and efficiently. Based on observations in the field regarding the data collection process, which is still manual, the researchers will be able to design a patient referral information system with software development tools using database design with MySQL, while programs can use PHP. The researchers in this study used a data collection method, such as interviewing several related parties. This information system design will make it easier for hospital managers in the next stage to develop an information system so that it can be used to process patient referral system data and present computerized information as a whole and efficiently.